THE USING OF OPEN ENDED LEARNING MODEL WITH MULTIMEDIA IN IMPROVING NATURAL SCIENCE LEARNING ABOUT ENERGY AND CHANGE AT FOURTH GRADE STUDENTS OF SDN 3 SELANG IN THE ACADEMIC YEAR OF 2014/2015 - Pratiwi, Friesca Aster (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Using of Open Ended Learning Model with Multimedia in Improving Natural Science Learning about Energy and Change at Fourth Grade Students of SDN 3 Selang in the Academic Year of 2014/2015. This research aims to: describe the steps of Open Ended Learning model with multimedia, improve natural science learning by applying Open Ended Learning model with multimedia, find problems and solutions in the using of Open Ended Learning model with multimedia. This collaborative Classroom Action Research (CAR) conducted in three cycles. The subjects of this research were 21 students of the fourth grade in SDN 3 Selang. The conclusion is the using of Open Ended Learning model with multimedia implemented with appropriate steps can improve natural science learning about energy and change at fourth grade students of SDN 3 Selang in the academic year of 2014/2015. Keywords: Open Ended Learning Models, Multimedia, Learning, Natural Science.